2022
DOI: 10.3390/molecules27175725
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Interferon-Gamma Aptamer with Good Affinity and Analytical Utility by a Rational In Silico Base Mutagenesis Post-SELEX Strategy

Abstract: The Systematic Evolution of Ligands by EXponential enrichment (SELEX) is conventionally an effective method to identify aptamers, which are oligonucleotide sequences with desired properties to recognize targets specifically and sensitively. However, there are some inherent limitations, e.g., the loss of potential high-affinity sequences during biased iterative PCR enrichment processes and the limited structural diversity of the initial library, which seriously restrict their real-world applications. To overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Xie et al [58] adopted carboxylated magnetic beads for HBsAg immobilization by some deoxynucleotide aptamers which can bind with high specificity to the surface antigen of hepatitis B virus (HBV) [59]. In immobilized metal affinity chromatography (IMAC), metal ions such as Zn(II), Cu(II), Ni (II), and Co(II) are immobilized on a support to fractionate and purify proteins in solutions; the IMAC method is used to enrich most of the phosphopeptides from whole cell lysates, and it is reported that titanium dioxide (TiO 2 ) beads have an equivalent ability to enrich phosphopeptides [60,61].…”
Section: Affinity Selexmentioning
confidence: 99%
“…Xie et al [58] adopted carboxylated magnetic beads for HBsAg immobilization by some deoxynucleotide aptamers which can bind with high specificity to the surface antigen of hepatitis B virus (HBV) [59]. In immobilized metal affinity chromatography (IMAC), metal ions such as Zn(II), Cu(II), Ni (II), and Co(II) are immobilized on a support to fractionate and purify proteins in solutions; the IMAC method is used to enrich most of the phosphopeptides from whole cell lysates, and it is reported that titanium dioxide (TiO 2 ) beads have an equivalent ability to enrich phosphopeptides [60,61].…”
Section: Affinity Selexmentioning
confidence: 99%
“…In the biomedical field, these devices have enabled the detection and quantification of biological molecules such as proteins and nucleic acids with high accuracy and in real time [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. They have also enabled the development of point-of-care devices that can rapidly diagnose diseases and monitor treatment outcomes [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%